Thermodynamic analysis of chemical heat pumps. (August 2015) - Obermeier, Jonas; Müller, Karsten; Arlt, Wolfgang
Abstract: Thermal energy storages and heat pump units represent an important part of high efficient renewable energy systems. By using thermally driven, reversible chemical reactions a combination of thermal energy storage and heat pump can be realized. The influences of thermophysical properties of the involved components on the efficiency of a heat pump cycle is analysed and the relevance of the thermodynamic driving force is worked out. In general, the behaviour of energetic and exergetic efficiency is contrary. In a real cycle, higher enthalpies of reaction decrease the energetic efficiency but increase the exergetic efficiency. Higher enthalpies of reaction allow for lower offsets from equilibrium state for a default thermodynamic driving force of the reaction. Highlights: A comprehensive efficiency analysis of gas-solid heat pumps is proposed. Link between thermodynamic driving force and equilibrium drop is shown. Calculation of the equilibrium drop based on thermochemical properties. Reaction equilibria of the decomposition reaction of salt hydrates. Contrary behavior of energetic and exergetic efficiency.